Antibiotic susceptibility pattern and risk factors associated with Acinetobacter and Pseudomonas infection at a tertiary care hospital - Sherchan, Jatan Bahadur (Journal of Kathmandu Medical College, 2021)
Background: Infection due to Acinetobacter spp. and Pseudomonas aeruginosa is a major worldwide concern these days. Antibiotic resistance and predisposing factors among the patients for acquiring such infection is a major challenge globally and in Nepal. Objectives: To determine antimicrobial susceptibility pattern of Acinetobacter spp. and Pseudomonas aeruginosa isolates along with predisposing factors. Methods: A total of 9,705 clinical samples were processed in this analytical cross-sectional study from December 2019 to November 2020. Antibiotic susceptibility pattern was determined following Clinical Laboratory Standard Institute guidelines. Patients’ information was obtained after informed consent. Results: Acinetobacter spp. and Pseudomonas aeruginosa isolates were 92 (0.95%). Fifty-three (57.61%) samples were respiratory samples. Thirteen (20%) Pseudomonas aeruginosa and 18 (66.67%) Acinetobacter spp. were multidrug-resistant (MDR). Eight (12.31%) Pseudomonas aeruginosa strains and 13 (48.15%) Acinetobacter spp. strains were sensitive only to Colistin. Twenty-two (95.65%) prolonged hospital stayers had MDR bacteria compared to only nine (13.04%) non-prolonged hospital stayers (p-value <0.001). Sixteen (94.12%) of diabetic patients had MDR bacteria isolates in comparison to only 15 (20%) of non-diabetic patients (p-value <0.001). Thirty-one (33.69%) were elderly patients (age ?65 years) and 61 (66.31%) were of age less than 65 years old. Seventeen (54.84%) of elderly patients had MDR isolates whereas only 14 (22.95%) of patients who are not elderly had MDR isolates (p-value =0.0047). Conclusion: Acinetobacter spp. and Pseudomonas aeruginosa strain were isolated from various samples. For effective treatment of infection by such organisms detailed microbiological diagnosis and drug susceptibility testing is needed along with identification of predisposing factors.